PENGARUH EDKASI FIRST AID TERHADAP PENGETAHUAN IBU TENTANG LUKA BAKAR DI DUSUN TRAYEMAN KELURAHAN PLERET YOGYAKARTA: Pengaruh Edukasi “First Aid” Terhadap Pengetahuan Ibu Rumah Tangga Tentang Penanganan Luka Bakar Di Dusun Trayeman Kelurahan Pleret Yogyakarta - Tomayahu, Widya; Setyaningrum, Niken (Ruang Ide Publisher, 2023)
Abstrak Background. The death rate due to burns in the world continues to increase every year, including Indonesia. This increase is accompanied by a high risk of women experiencing burns, this is because they cook using unsafe stoves and open fires. The incidence of burns can be influenced by several things, namely heat, radiation, electricity and chemistry. One way to be able to improve treatment in the incidence of burns is to provide first aid. First aid in burns that are not appropriate can have an impact that will harm the sufferer. Success in providing treatment for burns at home is done by increasing public knowledge (especially housewives) regarding first aid for burns. This study aims to determine the influence of first aid education on housewives' knowledge about burns in Trayeman hamlet, Pleret Village, Yogyakarta. Method. This study used a pre-experimental research design with a one group pretest and posttest approach. The sample technique uses total sampling. The study population is housewives in the hamlet of Trayeman rt. 03 Pleret Village Yogyakarta. With a sample of 41 respondents. Data analysis using Wilcoxon Signed Rank Test. Results. There is an influence of first aid education on housewives' knowledge about burn management in Trayeman hamlet, Pleret Village, Yogyakarta with a value of p-value = 0.000 (<0.05). Conclusion. Housewives' knowledge of first aid in burns can be improved by providing first aid education about burns. It is expected for further researchers to be able to develop educational methods such as by providing education accompanied by practice or demonstration related to first aid burns.